PENYELESAIAN SENGKETA INTERNASIONAL MELALUI KEKUATAN BERSENJATA OLEH PERSERIKATAN BANGSA-BANGSA DALAM MENJAGA PERDAMAIAN DUNIA - Melda Theresia Sihombing; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRAK International relations that happened among states are not always goes well. Disputes happen in this relations frequently.To solve this disputes, we can use of force. Use of force is not suggested, but it is not  forbidden too. International disputes settlement by use of force can be devide became two kind, they are unilateral and collective. Unilateral method can be done by each state without getting permission from any party, but this method must be done in individual self-defence situation. Collective method must be done by the Resolution from Security Council of United Nation. The international disputes settlement, neither it is solve by the unilateral method or collective method, we can see the regulation in Chapter 51 United Nation Charter.